i'd be really grateful if someone could complete this simultaneous equation with working out explaining each stage of the process. thanks.
y = 2x + 3
x2 + y2 = 2
You mean this?
$\displaystyle y\,=\,2x\,+\,3$
$\displaystyle x^2\,+\,y^2\,=\,2$
Plug the first equation into the second where you see the y:
$\displaystyle x^2 + (2x + 3)^2 = 2$
Solve for x:
$\displaystyle x^2 + 4x^2 + 12x + 9 = 2$
$\displaystyle 5x^2 + 12x + 7 = 0$
$\displaystyle (x + 1)(5x + 7) = 0$
Set each factor equal to 0 and you'll get
$\displaystyle x = -1$ or $\displaystyle x = {-\frac{7}{5}}$
Plug both values into the first equation to get the corresponding y values.
EDIT: Beaten to it!
cheers guys. appreciate the help.
the only bit i'm not too sure on is how to get from
x2 + (2x+3)2 = 2 to
x2 + 4x2 + 12x = 9 =2
would really appreciate if you could explain what i have to do.
thanks.